EFFECT OF ORGANIC, CHEMICAL FERTILIZERS AND PLANT DENSITY ON: 2- SOME GROWTH AND YIELD CHARCTERISTICS OF CAULIFLOWER Brassica oleracea var. botrytis - Al-Zuhairy, Haneen TH.; AL-Hamdany, Sabeeh A. (Diyala Agricultural Sciences Journal, 2017)
The Experiment was carried out at College of Agriculture, University of Diyala during autumn season 2014 to investigate the effects of two factors the fertilization, plant densities and their interactions a combination on growth and yield of cauliflower. The Experiment included 12 treatment represent between tow plant densities, the first represented in planting cauliflower seedlings on one side of drip tube, The second was planting seedling on both sides of the drip irrigation tubes. six fertilizers treatments were applied included: control (without fertilizer), sheep manure at 2.5, 5, 7.5 and 10% of soil volume (soil volume was calculated on the basis of experimental unit area at 0.3 m depth) and the treatment of chemical fertilizer NPK 20:20:20 according to a recommendation 300kg ha-1 which was added at two times: first one added one week after planting in the field, second was added at curds appearance. This Experiment was designed in Factorial Experiment according the with three replicates means were compared according to Duncan's Multiple Range Test at the probability level 0.05. Result could be summarized as follows: the first density planting caused significantly increased in the leaves fresh weights, curd diameters, curd weights with leaves and leaves content of N before curds became visible and after to 0.79 kg plant-1, 20.10cm, 1.85Kg plant-1, 2.47% and 2.45% respectively. as compared with the second density which reduced the last to 0.51kg Plant-1, 15.34cm, 1.03 kg plant-1, 2.11% and 1.36% respectively, otherwise, second density has a significant effect on the height plant and total yield (curds with leaves) which is 40.92cm and 57.41 ton ha-1 respectively as compared with first density 38.01cm and 51.44 ton ha-1. The addition of sheep manures level of 10% increase in the height plant, leaves fresh weights, curd diameters, curd weights with leaves, total yield (curds with leaves) and leaves content of N before curds became visible and after to 48.60 cm, 0.86kg plant-1, 21.25cm, 2.14 kg plant-1, 80.42 ton ha-1, 2.67% and 2.21% respectively, as compared with no fertilizer which reduced the number of it to 34.89 cm, 0.43 kg plant-1, 15.18cm, 0.83 kg plant1-, 30.14 Ton ha-1, 1.59% and 1.24% respectively. Treatment interaction between the first density and sheep manures 10% gave a significant increase in the last characteristic respectively, as compared with treatment interaction between the second density and no fertilizer